2013
DOI: 10.1097/jom.0000000000000045
|View full text |Cite
|
Sign up to set email alerts
|

An Employee Total Health Management–Based Survey of Iowa Employers

Abstract: Objective To implement an Employee Total Health Management (ETHM) model-based questionnaire and provide estimates of model program elements among a statewide sample of Iowa employers. Methods Survey a stratified random sample of Iowa employers, characterize and estimate employer participation in ETHM program elements Results Iowa employers are implementing under 30% of all 12 components of ETHM, with the exception of occupational safety and health (46.6%) and worker compensation insurance coverage (89.2%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 10 publications
(11 reference statements)
1
11
0
Order By: Relevance
“…Overall, the presence of selected organizational safety policies was higher than governance and planning strategies, a result consistent with similar studies [18,32]. The observed higher adoption of policies related to seatbelt use and cell phone/texting while driving in the ‘Construction’ and ‘Transportation and Warehousing’ sectors was expected considering these workers are more likely to engage in work-related travel.…”
Section: Discussionsupporting
confidence: 88%
“…Overall, the presence of selected organizational safety policies was higher than governance and planning strategies, a result consistent with similar studies [18,32]. The observed higher adoption of policies related to seatbelt use and cell phone/texting while driving in the ‘Construction’ and ‘Transportation and Warehousing’ sectors was expected considering these workers are more likely to engage in work-related travel.…”
Section: Discussionsupporting
confidence: 88%
“…5 More recently, the RAND Workplace Wellness Programs survey had a response rate of 19%, 6 the Kaiser Employer Health Benefits Survey had a 17% response rate among first-time respondents, 9 and the Employee Total Health Management survey (fielded with Iowa employers in 2012) had a response rate of 21.5%. 31 We conducted a nonresponse bias analysis for known characteristics (size, industry, and region) of responding and nonresponding worksites and found no systematic differences. If the survey outcomes of interest are related to other, unknown characteristics, there is potential for bias.…”
Section: Discussionmentioning
confidence: 94%
“…Previous research has shown that several factors can lead to work-related accidents-e.g., as the company size increases, the incidence rate decreases due to the provision of better occupational health and safety programmes [32]-and thus various algorithms have been developed for safety engineering, such as the opposite degree algorithm [33] and neural network [34]. In addition, the limited enforcement of safety regulations can affect workers' safety conditions [35].…”
Section: Distal Causementioning
confidence: 99%